MICROBIOLOGICAL ACTIVITY OF SOILS OF SOUTHERN FERGANA AND THE INFLUENCE OF VARIOUS FACTORS ON IT (Scientific journal of the Fergana State University, 2025)
The article presents data on microbiological activity, including the number of different taxonomic and physiological groups of microorganisms and its change under the influence of various factors. It has been established that the number of microorganisms is higher in the upper soil layers and sharply decreases along the soil profile from top to bottom. An increase in the humus content in the soil has a positive effect on the number of microorganisms. At the same time, the granulometric composition of the soil significantly affects the number of microorganisms. An increased content of microorganisms in the upper soil horizon increases the activity of microbiological processes and soil formation in this horizon.